2000
DOI: 10.1007/bf03028224
|View full text |Cite
|
Sign up to set email alerts
|

Microbiologically influenced corrosion of underground pipelines under the disbonded coatings

Abstract: The microbiologically influenced corrosion (MIC) of underground pipeline was identified. Corrosion was typically found under the disbonded area of girth welds coating where cathodic protection (CP) current could not penetrate. Sulfate reducing bacteria (SRB) and fermentative acid producing bacteria (APB) were confirmed as the microbes involved in the corrosion process. This corrosion occurred despite the fact that the CP level was well below the criteria of -850 mV (Cu/CuSO4). Detailed field surveys and labora… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
25
0
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(29 citation statements)
references
References 8 publications
(8 reference statements)
0
25
0
1
Order By: Relevance
“…First, iron in anoxic environments containing sulfate, i.e., the electron acceptor of SRB, is particularly prone to microbial corrosion ( Fig. 1) (37,53,54). Second, SRB, or their characteristic corrosion product FeS, are ubiquitously found on anaerobically corroded iron (54)(55)(56)(57)(58)(59).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…First, iron in anoxic environments containing sulfate, i.e., the electron acceptor of SRB, is particularly prone to microbial corrosion ( Fig. 1) (37,53,54). Second, SRB, or their characteristic corrosion product FeS, are ubiquitously found on anaerobically corroded iron (54)(55)(56)(57)(58)(59).…”
mentioning
confidence: 99%
“…1) (37,53,54). Second, SRB, or their characteristic corrosion product FeS, are ubiquitously found on anaerobically corroded iron (54)(55)(56)(57)(58)(59). Third, with corrosion rates of up to 0.9 mm Fe 0 year Ϫ1 (35 mils per year [mpy]), pure laboratory-grown SRB cultures corrode iron to an extent (12,60,61) that matches even severe cases of corrosion in the field.…”
mentioning
confidence: 99%
“…Elektrochemische Korrosion läuft überwie-gend unter aeroben Bedingungen ab, während mikrobiell induzierte Korrosion (MIC) insbesondere auch unter anaeroben Bedingungen auftritt. Zur Korrosionsvermeidung (Hamilton 1985;Heitz et al 1996;Heitz und Sand 1997;Li et al 2000) wurden zwar beständigere Werkstoffe und Schutzmaßnahmen entwickelt (Sand 2001;Stadler et al 2008), dennoch sind Schäden nach wie vor von großer wirtschaftlicher Bedeutung. Dies trifft besonders für geothermische Anlagen zu, bei denen aus Kostengründen häu-fig Schwarzstahl verwendet wird.…”
Section: Mikrobiell Induzierte Korrosion (Mic) In Geothermischen Anlagenunclassified
“…Many studies have shown that a high degree of sulphate-reducing bacteria (SRB)-induced corrosion occurs under most disbonded coatings [17][18][19][20][21]. The electrolyte trapped under a disbonded coating provides a suitable environment in which such microorganisms can exist because the essential components for their metabolism are present in this environment: a carbon source, water, an electron donor, and an electron acceptor [17].…”
Section: Introductionmentioning
confidence: 99%